Brain [18F]Fluorodeoxyglucose Metabolism Assessment under Hypothyroidism and Recombinant Human Thyroid-Stimulating Hormone in Comparison with Thyroid Hormone Replacement in Patients Submitted to Total Thyroidectomy - Sílvia D. Almeida; Francisco P. M. Oliveira; Maria J. Oliveira; José M. Oliveira; Rita Afonso; Diogo B. Faria; Durval C. Costa (Applied Sciences, 2022)
Objective: To compare brain metabolism using [18F]fluorodeoxyglucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT) in total thyroidectomy patients during hypothyroidism (levothyroxine withdrawal) or under recombinant human thyroid-stimulating hormone (rhTSH) against levothyroxine intake. Methods: A total of 12 patients were randomly divided into two groups. One group underwent the first [18F]FDG PET/CT brain scan after levothyroxine withdrawal (hypothyroidism condition) and repeated the scan 6 months later during regular levothyroxine intake (replacement condition). The other group underwent the first [18F]FDG PET/CT scan after receiving an rhTSH injection and maintained regular levothyroxine intake (rhTSH condition), and repeated the scan 7 months later during regular levothyroxine intake without rhTSH administration. The intra-group regional brain metabolisms were compared. Results: Under the hypothyroidism condition, brain metabolism was significantly reduced, namely in the bilateral pre-frontal, temporal, anterior cingulate, and primary motor cortices, insula, and striatum (uncorrected voxelwise p < 0.005); No significant differences were found between the rhTSH and replacement conditions. Conclusion: rhTSH administration could be a better option than levothyroxine withdrawal for 131I treatment, serum thyroglobulin measurement, or radioiodine scanning for patient follow-up.